GEOINFORMATION SYSTEMS IN FOREST RESOURCES MONITORING - Savkov, P.; Levinskova, N.; Bondarchuk, G.; Postarnichenko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The total area of the forest fund of Ukraine is 10400000 hectares, of which 9600000 hectares are covered with forest vegetation. In total, 15.9 % of the country's area is covered by forests. This figure is growing: in 50 years the area of forests increased by 21 %, almost three times increased stock of wood – it is estimated within 2102 million cubic meters. But this is not enough. Today there are a number of problems connected with forestry, for example: mass destruction of forests, lack of forest development strategy, low level of forest resources use, lack of reliable information about the biomass condition, forest fires. According to the State Agency of Forest Resources of Ukraine, the volume of unauthorized felling has been steadily decreasing for a long time, during 2005-2010. However, already in 2011 it was 25,100 cubic meters, which is 2.2 thousand more than in the previous year, 2007. However, this statistic, too, is mostly about illegal logging by local people, so it reflects very small volumes. The largest number of poached logging is recorded in the Lviv region. For example, in 2018 in the region 12,047 cubic meters of wood were illegally cut, and the figures do not stand still. As a consequence, this situation over time can lead to environmental degradation, increased water and wind erosion, degradation of agricultural land. The forest industry is one of the promising industries in Ukraine, for which it is advisable to use the tools of geographic information systems that provide detailed and necessary information, which greatly simplifies the work in research, analysis and prediction of the dynamics of the forestry fund of Ukraine. With the help of geospatial analysis tools we open up new horizons in the development and organization of forestry production, control and management of forests at all levels. This is why in today's conditions the introduction of geoinformation technologies can not only save money, but also save large areas of the forest fund and hundreds of diligent villages, settlements and cities. The events that took place in April 2020 showed that the lack of active monitoring of burning areas has painful consequences. The fire destroyed almost 40 houses in the resettled villages, Lichmans Srednyaya Rudnya, Nizhnyaya Rudnya and Verkhnyaya Rudnya, 45 buildings were saved, about 5 % of the protected area, 11500 hectares in the southwestern part of the Chernobyl Reserve were affected. These villages in Zhytomyr region were resettled after Chernobyl. More than 2000 people and 120 units of equipment were involved in extinguishing the fireі.
Keywords: geographic information system, forest, forest fund, forest fires, GIS